Analysis of Acetylcholinesterase Gene Expression in Male Mice Exposed to Sublethal Dose of Endosulfan Pesticide - Abd_Alkazem, Diyana M.; Rabee, Adel M. (Iraqi Journal of Science, 2023)
The aim of the current study was to investigate endosulfan effects on the Acetylcholinesterase (AChE) enzyme and gene in albino mice. Thirty selected male albino mice were randomly divided into 3 groups. The first group was control group (G1), while the other two treated groups were injected intraperitoneally twice per week with two doses of endosulfanG2 (3 mg/kg) and G3 (17 mg/kg) for 21 and 45 days respectively. The results recorded a significant decrease in AChE enzyme in the group treated with 17 mg/kg b.wt. (3986.67 ±170.32 U/L),compared to the control (5584.33 ±140.35 U/L)and treatment group with 3 mg/kg b.wt.(5556.00 ±341.01) U/L for 21 days. Also, there was a significant decrease in the enzyme level between the two treated groups (4688.00 ±221.49 U/L)and (3413.67 ±305.42 U/L) for the duration of 45 days of the dose, compared with the control group (5584.33 ±140.35 U/L), and increased expression of AChE gene in the treated groups.Gene expression fold in all treated groups was higher than in the control group withthe highest recorded value of 14.320at 17 mg/kg for 45 days, compared with the control group.